The dynamic behaviour of ballistic gelatin - Shepherd, C. J.; Appleby-Thomas, Gareth J.; Hazell, Paul J.; Allsop, Derek F. (American Institute of Physics (AIP), 2009)
In order to characterise the effect of projectiles it is necessary to understand the mechanism of both penetration and resultant wounding in biological systems. Porcine gelatin is commonly used as a tissue simulant in ballistic tests because it elastically deforms in a similar manner to muscular tissue. Bullet impacts typically occur in the 350–850 m/s range; thus knowledge of the high strain-rate dynamic properties of both the projectile and target materials are desirable to simulate wounds. Unlike projectile materials, relatively little data exists on the dynamic response of flesh simulants. The Hugoniot for a 20 wt.% porcine gelatin, which exhibits a ballistic response similar to that of human tissues at room temperature, was determined using the plate-impact technique at impact velocities of 75–860 m/s. This resulted in impact stresses around three times higher than investigated elsewhere. In US−uP space the Hugoniot had the form US = 1.57+1.77 uP, while in P−uP space it was essentially hydrodynamic. In both cases this was in good agreement with the limited available data from the literature.
Shock Compression of Condensed Matter 2009: Proceedings of the American Physical Society Topical Group on Shock Compression of Condensed Matter, 28 June - 3 July 2009, Nashville, TN, USA
Keywords: Shock compression; equation of state; ballistic gelatin